Regional Stratigraphic correlation and comparison of the Oligo-Miocene deposits in Dezful (SW Iran) and Kirkuk (N and NE-Iraq) embayments - Soltani, B.; Bonab, H. Rahimpour-; Ranjbaran, Bonab M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
The Oligo-Miocene deposits and their equivalents are one of the most important petroleum systems of the Middle-East, especially Iran and Iraq. In this paper, correlation between these important deposits has been discussed stratigrphically and sedimentologically, with some case studies (in outcrop and subsurface) in SW Iran and N, NE Iraq. Lithologically, the most thickness of the Asmari Formation (Oligo-Miocene) in Iran is deposited in Dezful area. These deposits, consist of shallow carbonate and they are lateral equivalent of Kirkuk group and Euphrates, Dhiban and Jeribe Formations in north and northeastern of Iraq. Microfacies analysis and depositional environments of these deposits are compared in terms of sequence stratigraphy. It appears that there are the relationship between Dezful and Kirkuk embayments in the mentioned period. The study demonstrated that the deposits in SW Iran and N, NE Iraq are almost the same with some minor discrepancies.
Keywords: OligoMiocene Correlation Dezful embayment; SW Iran Kirkuk embayment; N; NE Iraq